The scientific foundation of neuropsychological assessment : with applications to forensic evaluation - Russell, Elbert W. (Elsevier, 2012)
Neuropsychology is a specialized branch of psychology which focuses on the relationship between the brain and human functions including cognition, behaviour, and emotion. With an emphasis on a scientific approach which includes analysing quantitative data, neuropsychology follows an information processing approach to brain activity using standard assessments to evaluate various mental functions. This book examines the standardized battery of tests in neuropsychology, with a particular focus on forensic applications of these tests, suggesting that a united theory of assessment needs to be estab.